2019
DOI: 10.3389/fpubh.2019.00124
|View full text |Cite
|
Sign up to set email alerts
|

Early Success With Retention in Care Among People Living With HIV at Decentralized ART Satellite Sites in Yangon, Myanmar, 2015–2016

Abstract: Introduction: Myanmar is one of the countries in the Asia-Pacific region hit hardest by the HIV epidemic that is concentrated among urban areas and key populations. In 2014, the National AIDS Programme (NAP) launched a new model of decentralized service delivery with the establishment ART satellite sites with care delivered by HIV peer workers. Methods: ART satellite sites are implemented by non-government organizations to service high burden HIV areas and populations that su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Questionnaire At baseline, this study found that the global health status/QOL of all participants was fair with a mean score of 61.8 ± 20.1. It was comparable to the reference value of 61.8 ± 24.6 which was reported in a 49 countries study by the EORTC group (Scott et al, 2008), but lower than the scores in previous Myanmar study (Htet, 2016) and Morocco study (El Fakir et al, 2016) (66.1 ± 21.2 and 68.5 ± 18.5 respectively), and higher than in Egypt (RAM et al, 2018) and Iran (Shafaie et al, 2019b) studies (51.9 ± 25.7 and 59.1 ± 17.4 respectively).…”
Section: Global Health Status/qol Assessed By Eortc Qlq-c30supporting
confidence: 81%
See 3 more Smart Citations
“…Questionnaire At baseline, this study found that the global health status/QOL of all participants was fair with a mean score of 61.8 ± 20.1. It was comparable to the reference value of 61.8 ± 24.6 which was reported in a 49 countries study by the EORTC group (Scott et al, 2008), but lower than the scores in previous Myanmar study (Htet, 2016) and Morocco study (El Fakir et al, 2016) (66.1 ± 21.2 and 68.5 ± 18.5 respectively), and higher than in Egypt (RAM et al, 2018) and Iran (Shafaie et al, 2019b) studies (51.9 ± 25.7 and 59.1 ± 17.4 respectively).…”
Section: Global Health Status/qol Assessed By Eortc Qlq-c30supporting
confidence: 81%
“…The reference value for global health status/QOL among breast cancer patients by EORTC quality of life group was 61.8±24.6 in a total of 49 countries study (Scott et al, 2008). In Myanmar, the global health status/QOL scale among breast cancer patients was 66.08±21.19 (Htet, 2016).…”
Section: Introduction 11 Problem Statementmentioning
confidence: 94%
See 2 more Smart Citations
“…funding of the HIV response in Myanmar came from Global fund 13 . Nevertheless, the proportion of government spending on HIV increased threefold since 2012, representing 12% of the overall funding for HIV in 2015 13 In Myanmar, antiretroviral therapy (ART) has been provided free of charge at public and private NGO facilities 14 . Regarding ART provision, after HIV status was confirmed patients were enrolled and assessed for eligibility for ART initiation.…”
Section: Research Articlementioning
confidence: 99%